Siberian solar radiotelescope: the PCA format of the SSRT data compressor - Djourik, A.V.; Zhilin, P.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2003)
The present state of the art of lossless compression technology is given. The observed data format of the Siberian Solar Radiotelescope (SSRT) and an analysis of features of redundancy in raw data are discussed. Some of the methods used to model the signals are considered. The architecture of the developed compressor and the mathematical schemes for forecasting the signals at the stage of modeling are described. Some results of practical application of our approach are analyzed.